Kultura a osobowość organizacji - Barabasz, Adela (Culture and the personality of an organization, 2006)
Some fundamental assumptions concerning the concept of organizational personality are presented in the paper. The author shows that applying our knowledge of the phenomena and \ mechanisms governing the lives of individuals and groups may be useful in explaining phenomena and mechanisms arising in the realm of the functioning of an organization, specially international corporation. The paper shows the differences between concept of organizational culture and organizational personality. The viewing on an organization through the prism of the mechanisms of personality will allow management to exploit the potential of an organization more effectively.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1130, s. 309-318